Effects of water levels on plant traits and nitrogen use efficiency in monoculture and intercropped artificial grasslands - Wan, Zhiqiang; Gu, Rui; Yan, Yulong; Bai, Lijun; Bao, Tiejun; Yang, Jie; Gao, Qingzhu; Ganjurjav, Hasbagan; Hu, Guozheng; Zhou, Haijun; Chun, Xi (Frontiers in Plant Science, 2022)
Water availability is the main factor affecting the forage productivity of artificial grasslands, particularly in semi-arid regions. Generally, intercropping of gramineous grass and leguminous grass can achieve high productivity. However, how different water availability levels affect the productivity of intercropping system remains unclear. Here, we conducted a 3-year (2015–2017) study by manipulating the water conditions (CK equivalent to the annual precipitation, +50% treatment equivalent to 50% increase over the average precipitation, and −50% treatment equivalent to 50% decrease over the average precipitation) to explore the responses of plant traits, nitrogen use efficiency, and biomass of the monoculture of Medicago sativa (a leguminous grass, M.s), monoculture of Elymus nutans (a gramineous grass, E.n), and intercropping of M.s and E.n in a semi-arid region in Inner Mongolia, China. The results showed that the biomass obtained by intercropping of M.s and E.n decreased by 24.4% in −50% treatment compared to the CK treatment, while that of the monoculture of M.s decreased by 34.4% under the −50% treatment compared to the CK treatment. However, there was no significant difference in the biomass between intercropping artificial grassland and monoculture M. sativa under +50% treatment. Compared to monoculture, M.s can obtain more nitrogen by biological nitrogen fixation and decrease the proportion of nitrogen absorbed from soils under intercropping in the same water conditions. Under the intercropping system, the proportions of nitrogen absorbed from soils by M.s were 87.4%, 85.1, and 76.9% in −50%, CK, and +50% treatments, respectively. Under monoculture, these proportions were 91.9, 89.3, and 82.3% in −50%, CK, and +50% treatments, respectively. Plant trait, but not soil nitrogen content, was the main regulator for the productivity responses to water level changes. Our results highlight that intercropping can achieve higher productivity in both dry and wet conditions. Therefore, considering the fluctuating rainfall events in the future, it might be useful to alter the proportions of intercropped forage species in an artificial grassland to obtain optimal productivity by reducing the limitations of nitrogen availability. However, the economic viability of intercropping M. sativa and E. nutans should be evaluated in the future.